Prognostic implications of elevated pulmonary artery systolic pressure on 6-month mortality in elderly patients with acute myocardial infarction. Issue 4 (11th November 2022) - Wang, Shengji; Lian, Yonggang; Wang, Hongfei; Fan, Xiaoting; Zhao, Haiying
Abstract: Background: Pulmonary artery systolic pressure (PASP) has often been evaluated as an indicator of heart failure, but the relationship between PASP and the prognosis of elderly patients with acute myocardial infarction (AMI) is not well understood. Methods: The medical data of 3460 hospitalized elderly patients diagnosed with AMI between January 2013 and June 2018 were reviewed. PASP was calculated using transthoracic color Doppler ultrasonography. Patients were grouped according to their admission PASP results as follows: Group A, PASP ≤30 mmHg; Group B, 30 mmHg <PASP ≤50 mmHg; and Group C, PASP ≥51 mmHg. The primary endpoint was all-cause death 6 months following AMI. Multiple Cox regression analysis was used to identify independent risk factors for 6-month mortality in elderly patients with AMI. Results: PASP was associated with age, Killip classification, AMI site, and decreased ejection fraction in elderly patients. After adjusting for clinical and echocardiographic parameters in the Cox model, PASP was found to be significantly related to all-cause mortality. In receiver operating characteristic analysis, a PASP of >34 mmHg had a sensitivity of 62.3% and specificity of 65.7% for predicting 6-month all-cause death after AMI. Conclusion: PASP at admission is a useful marker for predicting short-term mortality in elderly patients with AMI. This finding could be used to help identify high-risk patients and make appropriate clinical decisions.